Analisis Tingkat Ketimpangan Ekonomi Kabupaten Banggai Kepulauan Menurut Willamson Index: Analysis of the Level of Economic Inequality in Banggai Islands Regency according to the Willamson Index - Rifaldi Mainggal; Yofandi Djibran Himran; Sri Rahayu Husen (Jurnal Ilmiah Produktif, 2020)
This study aims to determine the level of economic inequality in Banggai Islands Regency based on the Williamson Index analysis. The types and sources of data used in this study are quantitative data types and use secondary data sources. Secondary data obtained from the Central Sulawesi Province Central Statistics Agency 2016-2020. The analytical method used is the Williamson Index. The results of this study indicate that the level of economic inequality in the Banggai Islands district increases every year, in 2020 the Williamson Index shows a high inequality rate of 0.118 compared to the previous years which was relatively low, namely in 2016 the inequality rate only reached 0.080, in 2017 reached 0.081 in 2018 of 0.104 and in 2019 it reached 0.109. the average value of the Williamson Index in Banggai Islands Regency reached 0.208.